Aplicación web dinámica de los atractivos turisticos de la ciudad de Calceta del Cantón Bolívar provincia de Manabí - Álvarez Bermúdez, Andrea Valentina (2012)
The main objective of this work was to create a dynamic web application about the attractions of the city of Calceta in Bolivar to promote its tourist destinations with the purpose of encouraging visitors to come to its different tourist sites. The application allows users to find sites by presenting a dynamic view. Fordeveloping the application, the MIDAS (Model of Development of Web Information Systems) methodology was used. Information was gathered to define requirements and system architecture, then a storyboard was developed detailing the system content distribution. This procedure, together with the use of a free CSS template, allowed the application interface. Then the web database was built which coupled to the treatment and handling of information by MySQL 5.0.51a, dynamic functionality and services were also incorporated, for this, web development tools such as JavaScript 1.5., Jquery 1.7.1., PHP (Hypertext Preprocessor) 5.2.5 were used. The publication of the application in the domain http://www.turismocalceta.com corroborated the efficient functionality of this tool.